Modelagem para a mensuração de desempenho com base na satisfação de clientes da Brasilata S/A - Funke, Edson (2015)
The models of performance measurement help in decision-making, reflecting the organization's strategy into a set of measures which are capable of performing the measurement of its performance. In this scenario, the present work has the objective to propose a model of performance measurement based on the satisfaction of company's customers Brasilata S/A. This model is responsible for indicator of customer satisfaction from the perspective of the Balanced Scorecard (BSC). The proposed model consists in the application of a diagnostic for measuring the satisfaction indicator applied to customers of the company. The modeling presents in its assessment phase, the index of individual satisfaction of each customer, thus permitting the comparison and discussion of the results obtained. It is concluded that it is possible to measure and evaluate the level of satisfaction of customers of the company object of study through the use of the proposed model, where it is found that the overall rate of customer satisfaction reached the level of 98.68 %.